The Malvinas (Falkland) Islands revisited: The tectonic evolution of southern Gondwana based on U-Pb and Lu-Hf detrital zircon isotopes in the Paleozoic cover - Ramos, Victor Alberto (2017)
The first U-Pb and Hf-Lu isotopic data of detrital zircons from Devonian strata of the Malvinas (Falkland) Islands allow re-evaluation of different hypotheses regarding their location before the breakup of Gondwana. Of the various published hypotheses there are only two that have gained support. Adie's hypothesis involves a rotation of 180 degrees of the islands and a large displacement of Patagonia, independently of South America, whereas Borrello's hypothesis assumes a relative fixed position of the islands with respect to South America over time. The first hypothesis has traditionally been evaluated by highlighting the similarities of the geology of the Malvinas Islands with similar rocks cropping out in South Africa. In this paper we test those hypotheses that led to correlate the islands with the Cape System, based on geological, paleomagnetic and geochronological data. However, new isotopic data compared with contemporaneous Patagonian rocks, together with the present knowledge of offshore features of the Malvinas Plateau, suggest that its correlation with South Africa is not as compelling. Although there is no conclusive evidence, the simplest hypothesis based on the present available datasets, favors a closer relationship with Patagonia. No doubt that more research is needed in order to elucidate the paleogeography of the Malvinas Islands before the opening of the South Atlantic Ocean.